Hydrogen production and separation in fuel-rich operated HCCI engine polygeneration systems: Exergoeconomic analysis and comparison between pressure swing adsorption and palladium membrane separation - Dominik Freund; Ali Güngör; Burak Atakan (Applications in Energy and Combustion Science, 2023)
Hydrogen is one of the most important base chemicals and discussed as a future energy carrier for power and heat generation, as well as energy storage. Producing hydrogen at low costs and low CO2 emissions is thus of increasing importance. This study addresses the thermodynamics and economics of hydrogen, power, and heat generation by partial oxidation of methane in fuel-rich operated homogeneous charge compression ignition (HCCI) engines. Therefore, a python model of two different process concepts with different hydrogen separation technologies was developed and analyzed: pressure swing adsorption (PSA) and palladium membrane separation. The operating conditions of the engine and the separation were evaluated by conducting a global sensitivity analysis. The most suitable engine operating parameters were found at an equivalence ratio of 2, an intake temperature of 200 °C, a rotational speed of 1500 1/min, and a compression ratio of 22. In direct comparison, PSA consistently yielded better results than the palladium membrane, and low feed pressures were favorable. Subsequently, the uncertainty of economic input values was investigated and the power and hydrogen costs evaluated. In the PSA case, the electricity and hydrogen costs were found in a range of 44.2 €/MWh to 97.6 €/MWh and 2.7 €/kg to 7.2 €/kg, respectively, with an overall exergetic efficiency of 68.3%. Therefore, the proposed polygeneration system provides electricity at competitive costs and hydrogen at costs similar to a small-scale steam reforming plant at comparable efficiencies. Further scaling up of the engine could provide hydrogen at the cost of large-scale steam reforming, making the proposed concept a promising alternative.